Size- and temperature-dependent Young's modulus of individual ZnS nanobelts. (8th September 2022) - Ma, Liang; Jiang, Yijun; Dai, Guozhang; Mead, James L; Yibibulla, Tursunay; Lu, Mingyuan; Huang, Han; Fatikow, Sergej; Wang, Shiliang
Abstract: The Young's modulus of individual ZnS nanobelts with thicknesses ranging from 30 to 110 nm is measured by a mechanical resonance method over a temperature range of 300–650 K. Nanobelts with thicknesses above ∼80 nm exhibit a Young's modulus very close to their corresponding bulk value of 88 GPa, whilst thinner nanobelts with thicknesses down to 30 nm exhibit a Young's modulus of ∼70 GPa. Incrementally heating a nanobelt of 110 nm thickness over a temperature range of 300–650 K presents a linearly decreasing Young's modulus. The nanobelt is thus found to possess a temperature coefficient of Young's modulus of −125.4 ± 2.8 ppm K −1, which is comparable to their bulk value of −147 ppm K −1 . The temperature coefficient of Young's modulus for nanobelts with thicknesses below 100 nm demonstrates a strong size effect, and is found to dramatically decrease to as low as −201.4 ± 10.2 ppm K −1 for the thickness of 30 nm. A nonlinear temperature dependence of Young's modulus is experimentally identified for nanobelt with diameters below 100 nm, and the linear-nonlinear transition temperature decreases with the decrease of nanobelt thickness.